THE ROLE OF TENURE AND INCENTIVES ON EMPLOYEE BEHAVIOR - Utami Puji Lestari; Ella Anastasya Sinambela (Transpublika Publisher, 2021)
Every company needs to pay attention and regulate employee behavior in the workplace so that the stability of organizational life is maintained in a conducive manner. Various efforts have been made to achieve this, such as providing incentives. By paying attention to the adaptation of employees in the work environment based on years of service. The purpose of this study is to determine the role of tenure and incentives that shape employee work behavior. The selected population is all employees who work at a private bank branch office in Surabaya. All employees other than the leadership at the bank were sampled as many as 49 people. Regression analysis to answer the purpose of this study with the help of SPSS. The results obtained are the length of service and incentives together and individually proven to have a role to shape employee work behavior. The variable of tenure is more dominant in shaping employee work behavior.